Pengaruh Manajemen Sistem Pengelolaan Sampah Terhadap Peningkatan Mutu Pelayanan Publik Dinas Lingkungan Hidup Kota Malang - Syaikhul Khufat, Muhammad Devas; Warnidasari, Ririn; Firdaus, Belia Zahrotul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Malang City faces a significant increase in waste volume due to population growth and unsustainable consumption patterns, posing challenges in waste management and resulting in negative impacts such as environmental pollution and public health concerns.This encourages the Malang City Environmental Office to improve the quality of public services through effective and efficient waste management systems. This study aims to describe and analyze the effect of waste management system management on improving the quality of public services of the Malang City environmental agency. This research uses a qualitative approach with a literature study method. The results showed that the waste management system in Malang City has succeeded in improving the quality of life of the community and the reputation of the local government. This shows that effective waste management can provide significant benefits to the environment, communities, and local governments.